Author Correction: Re-examining tropical expansion. Issue 11 (November 2018) - Staten, Paul; Lu, Jian; Grise, Kevin; Davis, Sean; Birner, Thomas
In the version of this Review originally published, the affiliations for author Sean M. Davis were incomplete. An additional affiliation, "Cooperative Institute for Research in Environmental Sciences, University of Colorado at Boulder, Boulder, Colorado, USA", has now been added.